2019
DOI: 10.1007/s10681-019-2398-1
|View full text |Cite
|
Sign up to set email alerts
|

Wild barley shows a wider diversity in genes regulating heading date compared with cultivated barley

Abstract: Heading date (HD) is an important agronomic trait that influences plant adaptability to varying environment and, ultimately, grain yield. In this study, two doubled haploid (DH) populations were used to identify new QTL for HD. One of DH population is originated from a cross between an Australian malting barley cv. Franklin and a wild barley accession TAM407227 and the other one is from the cross between a Syrian wild barley SYR01 and an Australian malting barley cv. Gairdner. Using three times of sowing (TOSs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 80 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…This hypothesis is confirmed by our results that wild barley exhibits a rich genetic variation for high‐temperature tolerance. Likewise, Hu et al (2019) reported a high genetic variation for heading dates in wild barley in comparison with cultivated ones in three different sowing dates. It has also been hypothesized that wild genotypes that evolved in the warm climate of south‐west Iran with efficient high‐temperature tolerance strategies could be exploited as a rich genetic resource for improving heat stress tolerance in cultivated barley.…”
Section: Discussionmentioning
confidence: 90%
“…This hypothesis is confirmed by our results that wild barley exhibits a rich genetic variation for high‐temperature tolerance. Likewise, Hu et al (2019) reported a high genetic variation for heading dates in wild barley in comparison with cultivated ones in three different sowing dates. It has also been hypothesized that wild genotypes that evolved in the warm climate of south‐west Iran with efficient high‐temperature tolerance strategies could be exploited as a rich genetic resource for improving heat stress tolerance in cultivated barley.…”
Section: Discussionmentioning
confidence: 90%
“…31 . QTLRM-5H and QTLRM-7H were located at the same positions as the flowering time loci eam5 and Eps-7S , respectively 32 .…”
Section: Discussionmentioning
confidence: 91%
“…QTLZ-2H.2 was located at the same position as another QTL for heading date detected by Nduulu, et al 37 . QTLZ-5H and QTLZ-7H were located at the same positions as the flowering time genes eam5 and Eps-7S , respectively 38 .…”
Section: Discussionmentioning
confidence: 95%